Students’ Experiences on Learning Listening Through Youtube Media - Afrizal Afrizal; Rina Herlina (Journal of English Education Program (JEEP), 2023)
YouTube has become a fabulous learning medium for teachers to enhance students’ language abilities and to boost students’ listening skills. But, for some students, learning listening through YouTube is their first experience, mainly 7th-grade students in junior high school. It picked the interest of the researcher’s present study to explore the student’s experiences of learning listening through YouTube using a phenomenological design at one of the junior high schools in Karangpucung, Cilacap, Central Java. The data were obtained from observation and close-ended questionnaires to 32 EFL students who have experienced learning listening using YouTube in listening class. The findings showed that learning listening using YouTube in class is not hard to understand for students and it makes them feel more eager, joyful, and enthusiastic. Furthermore, students became more self-confident to communicate in English after learning listening through Youtube.